Nepal : Request for Disbursement Under the Rapid Credit Facility. - International Monetary Fund. Asia and Pacific Dept. (Washington, D.C. : International Monetary Fund, 2015)
This paper discusses Nepal's Request for Disbursement Under the Rapid Credit Facility (RCF). Before the April 2015 earthquake, Nepal's macroeconomic performance was broadly favorable but the government's weak budget implementation capacity held back growth and propped up the external position. The authorities' main challenge has been to boost their capacity to plan, prioritize, and implement capital spending. The authorities are requesting financial assistance under the IMF's RCF to address the urgent balance of payments and fiscal needs associated with the rehabilitation and reconstruction efforts. The IMF staff supports the authorities' request for a disbursement under the RCF in the amount of SDR 35.65 million.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet